A graph model for genomic prediction in the context of a linear mixed model framework - Montesinos-Lopez, Osval A.; Huerta Prado, Gloria Isabel; Montesinos-Lopez, José Cricelio; Montesinos-Lopez, Abelardo; Crossa, José (Wiley, 2024)
Genomic selection is revolutionizing both plant and animal breeding, with its practical application depending critically on high prediction accuracy. In this study, we aimed to enhance prediction accuracy by exploring the use of graph models within a linear mixed model framework. Our investigation revealed that incorporating the graph constructed with line connections alone resulted in decreased prediction accuracy compared to conventional methods that consider only genotype effects. However, integrating both genotype effects and the graph structure led to slightly improved results over considering genotype effects alone. These findings were validated across 14 datasets commonly used in plant breeding research.